The Unknown Larva of the Minute Diving Beetle Genus Brachyvatus Zimmermann, 1919 (Coleoptera: Dytiscidae: Bidessini) - Torres, Patricia Laura Maria (2013)
The three larval instars of Brachyvatus acuminatus (Steinheil, 1869) (the type species of the bidessine genus Brachyvatus Zimmermann, 1919) are described and illustrated for the first time including detailed morphometric and chaetotaxic analyses of the cephalic capsule, head appendages, legs, last abdominal segment and urogomphi. Larvae of this genus are characterized by the absence of the primary pore ABc, which is a synapomorphy of the tribe Bidessini. Brachyvatus larvae can be separated from those of all other known Bidessini genera by the following combination of characters: very small size; lateral branches of nasale well visible in dorsal view; ventroapical spinula on third antennomere absent; meso- and metatergite of instar I with anterotransverse carina; siphon short; long urogomphi with secondary setae; seta PA3 absent; setae UR2 and UR4 inserted contiguously; natatory setae present on tibiae in instars II–III.